2018
DOI: 10.1021/acs.jpcb.8b00321
|View full text |Cite
|
Sign up to set email alerts
|

Energy Renormalization for Coarse-Graining the Dynamics of a Model Glass-Forming Liquid

Abstract: Coarse-grained modeling achieves the enhanced computational efficiency required to model glass-forming materials by integrating out "unessential" molecular degrees of freedom, but no effective temperature transferable coarse-graining method currently exists to capture dynamics. We address this fundamental problem through an energy-renormalization scheme, in conjunction with the localization model of relaxation relating the Debye-Waller factor ⟨u⟩ to the structural relaxation time τ. Taking ortho-terphenyl as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 56 publications
(91 reference statements)
4
50
0
Order By: Relevance
“…We recently proposed an energy-renormalization (ER) approach to capturing AA polymer dynamics under coarse-graining 25,26 by renormalizing the cohesive interaction strength parameter ε (via the “entropy−enthalpy compensation” effect) 3438 in a temperature-dependent manner, i.e., ε(T)=α(T)ε0 where α( T ) is a renormalization factor and ε 0 is a constant value. The sigmoidal variation of α( T ) [and ε ( T )] obtained from our ER method is consistent with the variation of the extent of collective motion (or alternatively, the size evolution of the cooperatively rearranging regions) predicted by the GET of glass formation.…”
Section: Coarse-graining Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently proposed an energy-renormalization (ER) approach to capturing AA polymer dynamics under coarse-graining 25,26 by renormalizing the cohesive interaction strength parameter ε (via the “entropy−enthalpy compensation” effect) 3438 in a temperature-dependent manner, i.e., ε(T)=α(T)ε0 where α( T ) is a renormalization factor and ε 0 is a constant value. The sigmoidal variation of α( T ) [and ε ( T )] obtained from our ER method is consistent with the variation of the extent of collective motion (or alternatively, the size evolution of the cooperatively rearranging regions) predicted by the GET of glass formation.…”
Section: Coarse-graining Methodsmentioning
confidence: 99%
“…In our prior works, we demonstrated that by borrowing ideas from the generalized entropy theory (GET) and the Adam−Gibbs theory of glass formation, we could correct the accelerated dynamics of the CG model in a temperature-transferable manner. 25,26 This was done by realizing that E a can be “renormalized” by tuning the cohesive interaction strength parameter ε , which is readily accessible in commonly used nonbonded potentials such as the Lennard-Jones (LJ) potentials. The influence of ε on polymer dynamics has been vindicated in recent simulations.…”
Section: Introductionmentioning
confidence: 99%
“…We next turn to the issue of CG modeling of polymer melts within the framework of GET. The recent ER method provides an attractive approach for quantitatively describing the dynamics of the underlying AA polymer models under coarse‐graining over a wide temperature range 21,22,27. In the previous formulation of ER method, the CG models of polymers are developed by the exploiting the localization model of relaxation that relates the Debye–Waller factor (DWF; i.e., a fast‐dynamics property at a picosecond timescale) to τ α in MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the ER method has been recently tested for three distinct CG models of polymers having different segmental structures, that is, polybutadiene (PB), polystyrene (PS), and polycarbonate (PC), which can capture the AA dynamics to a good approximation 22. This method also works reasonably well for a model of a small‐molecule GF liquid, ortho‐terphenyl (OTP) 21. More details regarding the CG modeling via the ER method and its formulation can be found in our recent studies 22,27,48.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation